2011
DOI: 10.1111/j.1365-2265.2010.03957.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective echocardiographic evaluation of patients with endogenous subclinical hyperthyroidism and after restoring euthyroidism

Abstract: sHT was associated with significant changes in echocardiographic parameters, which may contribute to increased cardiovascular risk in these patients. The alterations were reversible with restoring biochemical euthyroidism, what supports the necessity of treatment introduction in sHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 35 publications
4
37
1
3
Order By: Relevance
“…Few studies have assessed the potential beneficial effects of TSH normalization on quality of life and cardiovascular and skeletal risk in SHyper.Some studiessuggest that cardioselective β-blockers [47,48] or treatment of SHyper with ATDs [46,67] may improve symptoms, heart rate and supraventricular arrhythmias in patients with grade 2 SHyper. A prospective study showed a significant improvement of cardiovascular parameters after treatment of hyperthyroidism [67].…”
Section: Treatment Of Endo Shyper: Effects Of Treatment With Atds Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have assessed the potential beneficial effects of TSH normalization on quality of life and cardiovascular and skeletal risk in SHyper.Some studiessuggest that cardioselective β-blockers [47,48] or treatment of SHyper with ATDs [46,67] may improve symptoms, heart rate and supraventricular arrhythmias in patients with grade 2 SHyper. A prospective study showed a significant improvement of cardiovascular parameters after treatment of hyperthyroidism [67].…”
Section: Treatment Of Endo Shyper: Effects Of Treatment With Atds Andmentioning
confidence: 99%
“…A prospective study showed a significant improvement of cardiovascular parameters after treatment of hyperthyroidism [67]. However, no long-term prospective controlled trials have assessed whether treatment reduces the risk of AF and other cardiovascular events.…”
Section: Treatment Of Endo Shyper: Effects Of Treatment With Atds Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Sgarbi 37 and Kaminski 40 performed similar analyses of cardiac disturbances before and after treatment of SH, using similar methods and arriving at concordant results. Both propose an early therapy of the SH, in order to prevent cardiac dysfunction and progression to advanced disease and to more concerning clinical effects.…”
Section: B Cardiovascular Effectsmentioning
confidence: 99%
“…Very recently Kaminski et al 40 evaluated the impact of SH in the heart through echocardiographic parameters. Patients were subjected to treatment with radio-iodine therapy.…”
Section: B Cardiovascular Effectsmentioning
confidence: 99%